Perencanaan Digital Branding dalam Penerimaan Peserta Didik Baru Menggunakan Analisis SWOT - Wahyuni, Tri; Annur, Saipul; Rohman, Asep (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to analyze the planning of digital branding in new student admissions (PPDB) using SWOT analysis at SMP Life Skill Teknologi Informatika Indo Global Mandiri Palembang and its implications for the effectiveness of PPDB. The background of this research is based on the increasing competition among educational institutions in the digital era, which requires schools to adopt adaptive, well-planned, and sustainable branding strategies. This study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that digital branding planning for PPDB is carried out through the formulation of clear objectives, SWOT-based analysis of the school’s internal and external conditions, and the development of consistent digital communication strategies. School strengths, such as A accreditation, the quality of human resources, and the effective use of digital media, serve as key factors in building a positive school image. Meanwhile, limitations related to budget and infrastructure are addressed through creative strategies and the optimization of social media platforms. Well-structured digital branding planning has been proven to enhance school visibility, public trust, and prospective students’ interest. This study concludes that SWOT-based digital branding planning has positive implications for the effectiveness of PPDB and can serve as a strategic reference for educational institutions in facing competition in the digital era.